The effects of the Malawi Farm Input Subsidy Program on household per-capita consumption convergence. Issue 3 (3rd April 2022) - Mwale, Martin Limbikani; Kamninga, Tony Mwenda; Cassim, Lucius
ABSTRACT: The Malawi Farm Input Subsidy Program (FISP) was praised for turning the country's food deficit into a surplus after inception in 2005. It is, however, not clear whether these food security gains spill over to equity in distribution of welfare. We examine the effects of the FISP on per-capita consumption convergence, on 2251 households interviewed in 2010–2013 Malawi Integrated Household Panel Survey. The analysis employs a Lewbel method of instrumental variables to account for non-random selection of beneficiaries into the programme. The results reveal that FISP helps relatively poor farmers increase household per-capita consumption towards converging to that of the relatively rich. This convergence is robust only among small but not large farmers. Past studies that evaluated the FISP while not paying attention to the welfare equity gains in household per-capita consumption, may have underestimated its benefits. Therefore, policy should support the programme with an additional objective of reducing inequality, beyond the primary aim of enhanced food security. Considering that the effects of FISP are limited to small farmers, alternative interventions such as inputs for credit should be made available to large farmers. This will allow FISP to induce widespread welfare gains.